Comparison Between computer Based Test (CBT) and paper Pencil Test (PPT) in Joint Admission Matriculation Board (JAMB): Case of Yola North Senatorial Zone of Adamawa State, Nigeria. - James, Afrifa; Yuguda, Hassan; Moses, Hannatu G; Jeremiah, Peter; Bitrus,, Ishaya (IJRDO -Journal of Computer Science Engineering, 2016)
Paper Pencil Test (PPT) was used to administer UTME to students who choose toapply to Nigerian public and private mono-technics, colleges of education, polytechnicsand universities by JAMB since its inauguration in 1978. Computer Based Test (CBT)was introduced in 2014/2015 session in UTME and sine then it has become a thing ofconcern to Nigerians as a result of very low computer literacy among students in seniorsecondary school. This study evaluated the comparability of PPT and CBT used byJAMB to administered UTME. The geographical scope is Adamawa south senatorialzone which includes Guyuk, Numan, Demsa, Lamurde, Mayo-belwa, Shalleng, Ganye,Jada and Tongo Local Government Areas Of Adamawa State. The questionnaireadministered contained 20 items as designed by the researcher. The questionnaire wasadministered to one thousand seven hundred and seventy five (1775) respondents fromseventy one (71) schools out of 96 schools in Adamawa South senatorial Zone. Simpleaverage method was employed to evaluate responses on the likert scale. The results